The need for smart microalgal bioprospecting - Joan Labara Tirado; Andrei Herdean; Peter J. Ralph (Natural Products and Bioprospecting)
Abstract Microalgae’s adaptability and resilience to Earth’s diverse environments have evolved these photosynthetic microorganisms into a biotechnological source of industrially relevant physiological functions and biometabolites. Despite this, microalgae-based industries only exploit a handful of species. This lack of biodiversity hinders the expansion of the microalgal industry. Microalgal bioprospecting, searching for novel biological algal resources with new properties, remains a low throughput and time-consuming endeavour due to inefficient workflows that rely on non-selective sampling, monoalgal culture status and outdated, non-standardized characterization techniques. This review will highlight the importance of microalgal bioprospecting and critically explore commonly employed methodologies. We will also explore current advances driving the next generation of smart algal bioprospecting focusing on novel workflows and transdisciplinary methodologies with the potential to enable high-throughput microalgal biodiscoveries. Images adapted from (Addicted04 in Wikipedia File: Australia on the globe (Australia centered).svg. 2014.; Jin et al. in ACS Appl Bio Mater 4:5080–5089, 2021; Kim et al. in Microchim Acta 189:88, 2022; Tony et al. in Lab on a Chip 15, 19:3810–3810; Thermo Fisher Scientific INC. in CTS Rotea Brochure). Graphical abstract